Parental involvement for better education: The relationship between parental awareness, emotional support, and children’s academic achievement at secondary level - Junaid Aman; Muhammad Babar Akram; Siti Mas'udah; Muhammad Saud; Yasir Nawaz Manj (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Students’ academic achievement greatly influenced by their parents’ socioeconomic status and involvement in their academic life. Regardless of the parents’ educational qualifications, their support helps the children gain confidence in education and then in life. This study intends to see the relationship between two independent variables: parental awareness and emotional support to children and one dependent variable: academic achievement. The study area is Jafarabad, a district in Balochistan, Pakistan. The sample size was 250, designated using the Taro Yamani formula, and a simple random sampling technique was used to choose the respondents. The questionnaire was then used to collect information. The collected data was then coded and analyzed in SPSS. Pearson correlation test was used to test the hypotheses. Significant findings show that the lack of parental awareness and interest in student’s school activities is the primary cause of their poor academic achievement at secondary school. Accordingly, the study concludes that it is the primary responsibility of parents to support their children and cooperate with school administration emotionally. Therefore, the government, specifically the district education office, and local NGOs need to run awareness campaigns on the importance of parental involvement in the children’s education, which will result in the children’s excellent academic achievement.